Understanding how hatred persists: situating digital harassment in the long history of white supremacy. Issue 11 (2nd November 2021) - Mott, Carrie; Cockayne, Daniel
Abstract: Racism, sexism, and homophobia have long been characteristic of liberal democracy in North America. Public discussion around harassment - with a particular focus on sexual violence against women - reached its ferment in the light of charges brought against a number of high-profile public figures and with the #MeToo movement. Within the academy, radical, feminist, and anti-racist scholars have recently faced targeted harassment and threats of violence through email campaigns organized online by right-wing and white supremacist online. Many have pointed to the specificity of the digital medium as facilitating new forms of harassment online. Yet, others have shown how digital spaces might be better seen in continuity with older forms of violence, that have long targeted communities of color working to challenge racist systems of oppression. We contribute to this line of thinking by examining a case of white supremacist violence against a Black family - the Wades - who purchased a home in a predominantly white neighbourhood in Louisville, Kentucky in the 1950s. With attention to both Black and digital geographies, we juxtapose the Wade's story with critical work on newer forms of white supremacy online. We show how hatred persists alongside shifts in medium, and question the extent to which digital platforms create new opportunities for harassment and violence.